Positive Solutions for Third-Order p-Laplacian Functional Dynamic Equations on Time Scales - Wen Guan; Da-Bin Wang (Abstract and Applied Analysis)
We study the following third-order p-Laplacian functional dynamic equation on time scales: Φp(uΔ∇(t))∇+a(t)f(u(t),u(μ(t)))=0, t∈0,TT,  u(t)=φ(t),  t∈-r,0T,  uΔ(0)=uΔ∇(T)=0, and u(T)+B0(uΔ(η))=0. By applying the Five-Functional Fixed Point Theorem, the existence criteria of three positive solutions are established.